1995
DOI: 10.5144/0256-4947.1995.317
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Maternal Mortality in Saudi Arabia

Abstract: A three year maternal mortality survey in Saudi Arabia has identified the various epidemiologic risk factors for maternal deaths. Unbooked, uneducated and economically underprivileged females were at increased risk of maternal death, especially >para 7 females, who were found to be at increased risk of maternal death, particularly deaths due to hemorrhage, pulmonary embolism and uterine rupture. In Saudi Arabia, there are contradictory risk factors for maternal death; e.g. low female literacy rate, early marri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
1
10
2
Order By: Relevance
“…In this study, MMR of 1543/100,000 live births is higher than reported by Shamshad 7 can also be applied here to improve the prospects of life in this regard. In contrast to reports from Bangladesh and Africa, 11 we found majority of deaths in age group>25 years -< 35 years. However, these findings correlate with other Pakistani studies 7 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In this study, MMR of 1543/100,000 live births is higher than reported by Shamshad 7 can also be applied here to improve the prospects of life in this regard. In contrast to reports from Bangladesh and Africa, 11 we found majority of deaths in age group>25 years -< 35 years. However, these findings correlate with other Pakistani studies 7 .…”
Section: Discussioncontrasting
confidence: 99%
“…However, these findings correlate with other Pakistani studies 7 . High parity has been reported as a risk factor for maternal deaths in developing countries 11 but, the current study did not find it as a risk factor. This can be probably related to the fact that most of the multiparous ladies usually have their deliveries at home and deaths could have been under reported.…”
Section: Discussioncontrasting
confidence: 95%
“…However, there were no cases of thromboembolism in our study. Currently, there is no national database for maternal mortality rates in Saudi Arabia but a single report based on statistics acquired during 1989–1992 quotes a rate of 18/100,000 12 with haemorrhage from placenta praevia as the dominant cause. Caesarean section reportedly contributed to 37% of direct maternal deaths, with more deaths due to emergency caesarean section (82%) compared with elective caesarean section (18%).…”
Section: Discussionmentioning
confidence: 99%
“…It is one of the causes of maternal death in many developing and developed countries [18,19,20] . This deficit in toxaemia-related knowledge among nurses may be explained due to the lack of exposure to actual cases of toxeamia.…”
Section: Discussionmentioning
confidence: 99%